Equipment and Rh blood factor in a group of native department of Junin - San Martín, Mauricio (1951)
The study of hereditary traits, such as blood group and Rh factor, if performed in adult individuals in a population; have value for a genetic interpretation, provided that the group studied is representative of the population that wants to know, because these characters are no differences in terms of age and is for this reason that in our work we have studied a group of 200 native-age military service procediían of areas near Huancayo, there being no factor to suspect some kind of insulation between the areas from which these individuals came.